Clinico-Pathological observational study of the spectrum of tumours of mesenchymal origin in the female genital tract - a prospective study in a tertiary care hospital - Dr. Manal Ashraf Ali; Dr. Swalaha Sadaf Siddique (Tropical Journal of Pathology and Microbiology, 2019)
Aim: The current study aims to evaluate uterine tumours of mesenchymal origin, their incidence, and to analysethe various gamut of clinical and histopathological findings which lead to diagnosis and optimal management. Material & Methods: A two year prospective study was conducted in the department of pathology in a tertiary care teaching hospital on mesenchymal tumors of the female genital tract, which were grossed, processed and reported. A case sheet for study was studied and analysed for statistical data. Result: 172 cases were reported in period of 2 years, common in multiparous women in their 4th decade of life, presented with menorrhagia, pain and dysmenorrhea, amongst which 95.93% were benign, 4.07% were diagnosed malignant on histopathology. Leiomyosarcoma, endometrial stromal sarcoma, smooth muscle tumour of uncertain malignant potential, carcinosarcoma were noted. Conclusion: Hysterectomy is routine procedure surgical procedure for gynaecological cause, and histopathological diagnosis is mandatory for multidisciplinary management of patient. Though the immunohistochemistry are supportive for diagnosis, but the morphological features trumphs all the ancillary testing required for diagnosis of mesenchymal origin of tumours.